2019
DOI: 10.15541/jim20180394
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Property of MoSi2-30Al2O3 Electrothermal Coating Prepared by Atmospheric Plasma Spraying

Abstract: With MoSi 2-30Al 2 O 3 mixed powders as the raw material, MoSi 2-30Al 2 O 3 electrothermal coating was sprayed by atmospheric plasma spraying technology. The phase composition, microstructure and thermal stability of the coating were systematically studied by XRD, SEM, electrical test and differential thermal gravity analysis. The results show that MoSi 2-30Al 2 O 3 electrothermal coating shows dense microstructure. Al 2 O 3 can improve the electrical resistivity and oxidation resistance of MoSi 2 materials in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…From the temperatures shown, it can be seen that the surface temperature of the heating pipe is relatively uniform. The temperature difference in the middle of the pipe is no more than 20 • C. The temperature difference between the edges and middle of the pipe is mainly due to the heat loss by thermal radiation and convection [22,32]. Figure 6a shows the pipe sample of TM15 electrical-heating coating.…”
Section: Lectrical-heating Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the temperatures shown, it can be seen that the surface temperature of the heating pipe is relatively uniform. The temperature difference in the middle of the pipe is no more than 20 • C. The temperature difference between the edges and middle of the pipe is mainly due to the heat loss by thermal radiation and convection [22,32]. Figure 6a shows the pipe sample of TM15 electrical-heating coating.…”
Section: Lectrical-heating Propertiesmentioning
confidence: 99%
“…The temperature difference in the middle of the pipe is no more than 20 °C. The temperature difference between the edges and middle of the pipe is mainly due to the heat loss by thermal radiation and convection [22,32]. Figure 7 shows the temperature-time curve of TM15 coating tested by five cycles of electrification.…”
Section: Lectrical-heating Propertiesmentioning
confidence: 99%
“…Researchers have carried out in-depth studies on the wave absorption performance and high-temperature oxidation of MoSi 2 . This research used MoSi 2 -30Al 2 O 3 as raw a material, prepared a MoSi 2 -Al 2 O 3 electrothermal coating by atmospheric plasma spraying, and studied the electrothermal properties of the composite coating [18]. Shang et al [19] prepared MoSi 2 /BC porous composite microwave absorbing material by the solid-phase sintering method and found that it had good absorbing performance.…”
Section: Introductionmentioning
confidence: 99%